A276 CLINCAL PREDICTORS FOR SESSILE SERRATED ADENOMA DETECTION: AN ANALYSIS OF 17, 524 COLONOSCOPIES. (15th March 2019) - Gandhi, M; Cocco, S; McDonald, C; Hindi, Z; Chakraborty, D; French, K; Siddiqi, O; Blier, M; Markandey, B; Siebring, V; Brahmania, M; Khanna, N; et al.
Abstract: Background: Adenoma detection and removal is crucial to prevent colon cancer. Although adenoma detection rate is the current benchmark, there is increasing interest in sessile serrated adenoma detection rate (SSADR) given sessile serrated adenomas (SSAs) are more difficult to identify endoscopically. Aims: To define predictors of SSA detection in a large colonoscopy cohort. Methods: We performed a prospective observational study using colonoscopy quality metrics collected by Cancer Care Ontario. All colonoscopies performed for any indication across 20 hospitals in Southwestern Ontario between April 2017 and February 2018 were identified. Data collected included patient demographics, procedural indication, bowel preparation, cecal intubation, endoscopist information, and histology of polyps removed. Cases without histology records were excluded. A multi-variable analysis was conducted to identify factors associated with SSA detection. Results: In total, 17, 524 colonoscopies (mean (SD) age = 59.6 (14.4), 53.9% female) were identified. At least one SSA was identified in 910 procedures, corresponding to a SSADR of 5.2%. On multi-variable analysis, variables independently associated with higher SSADR included increasing patient age (OR 1.02, 95% CI 1.02–1.03, p<0.001), cecal intubation (OR 3.80, 95% CI 1.87–7.71, p<0.001), use of split dose bowel preparation (OR 1.33, 95% CI 1.00–1.77, p=0.047), and very good bowel preparation quality (OR 2.48, 95% CI 1.38–4.44, p=0.002). Factors associated with lower SSADRs included non-screening colonoscopies (OR 0.55, 95% CI 0.48–0.63, p<0.001) and non-gastroenterologist endoscopist (general surgery OR 0.50, 95% CI 0.41–0.60, p<0.001; internal medicine OR 0.70, 95% CI 0.51–0.96, p=0.027; general practice OR 0.20, 95% CI 0.06–0.68, p=0.010). Conclusions: Modifiable factors associated with higher SSADRs include use of split dose bowel preparation, better bowel preparation quality, cecal intubation, and specialty of endoscopist. Ongoing initiatives emphasizing the importance of these variables should be encouraged. Funding Agencies: None